Amoris Laetitia: Towards a Methodological and Anthropological Integration of Catholic Social and Sexual Ethics - Salzman, Todd A. (Theological studies, 2018)
There is a long-noted anthropological and methodological divide between Catholic social and sexual ethics. We argue in three cumulative sections that Pope Francis' Amoris Laetitia moves towards an anthropological and methodological integration of Catholic social teaching and Catholic sexual teaching. First, we explore Amoris Laetitia's anthropological integration of Catholic social and Catholic sexual teaching; second, we explore its methodological integration of Catholic social and sexual teaching; finally, we demonstrate how the anthropological and methodological insights of Amoris Laetitia might provide a more integrated and credible response to a contemporary ethical issue.